PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II B SD NEGERI 62 PEKANBARU - Jufri, Ana Eliza; ', Hamizi; ', Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was held because Mathematics Learning Outcomes Class II B SD Negeri 62 Pekanbaru is low, as seen from the average value grade of 65.41. Of the 37 students, only 41% were completed and the remaining 59% did not complete. This proves that the average grade achieved a low student, because less than 72 which is a minimum completeness criteria (KKM). This happens because in the learning of teachers still use conventional methods to convey the subject matter. Based on these problems is necessary to study a class action by applying contextual learning model. This research aims to improve the Mathematics learning outcomes of students in Class II B SD Negeri 62 Pekanbaru with the application of contextual learning model with the number of students as many as 37 people consisting of 18 women and 19 men. This study consisted of two cycles. At each cycle I and II consist of 3 sessions consisting of two face-to-face meetings and one times daily test at the end of the cycle. With the implementation of contextual learning model can improve learning outcomes Math Class II B SD Negeri 62 Pekanbaru. Improving student learning outcomes in basic score students' average score was 65.41 (good), an increase in the first cycle to 76.62 (good), and increased again in the second cycle into 85.14 (very good). Application of contextual learning model can improve the quality of learning can be seen from the activities of teachers and students' activity increased at each meeting. The activities of teachers in the implementation of contextual learning in cycle 1 meeting 1 is 62.5% (good), and the second meeting was 68.75% (good). Whereas in cycle 2 meeting 1 is 75% (good), and the second meeting was 81.25% (very good). Student activity in the implementation of contextual learning in cycle 1 meeting 1 is 62.5% (good), and the second meeting was 68.75% (good). Whereas in cycle 2 meeting 1 is 75% (good), and the second meeting was 81.25% (very good). Based on the results of this study concluded that the application of contextual learning model can improve students' mathematics learning outcomes Class II B SD Negeri 62 Pekanbaru.Keywords : Contextual Learning Model, Learning Outcomes, Mathematic